Pemanfaatan Tumbuhan Obat Berpotensi Tinggi dalam Tradisi Oukup dengan Studi Index of Cultural Significance pada Masyarakat Karo di Kecamatan Kabanjahe Kabupaten Karo - Anastasiya Octavia Febrianti; Tri Harsono; Cicik Suriani; Ashar Hasairin; Muhammad Yusuf Nasution; Hendro Pranoto (Biocaster : Jurnal Kajian Biologi, 2026)
This research is a descriptive mixed-method ethnobotanical study aimed at identifying medicinal plants in the Oukup tradition of the Karo people based on the Index of Cultural Significance (ICS), analyzing utilization patterns, and analyzing community perspectives on their benefits and effectiveness. The research was conducted in Kabanjahe District through interviews and observations using a snowball sampling technique with 10 informants. Sixteen medicinal plant species were recorded, with the highest ICS score being ginger (50), followed by pepper (40), sappanwood (24), black ginger (20), and torch ginger (18). Plants are used in the form of rhizomes, stems, leaves, and fruits through boiling and steaming for postpartum recovery, increasing stamina, relaxing, warming the body, and reducing aches. The community positively assesses Oukup in terms of benefits, safety, and effectiveness, thus maintaining its relevance in the traditional health system and having the potential to be developed and preserved.